The Efforts to Improve Children’s Vocabulary through Bingo Game for 4–5-Year-Old Children at TK ABA Somawangi - Nur Chendah; Wafa Aerin (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Vocabulary ability is one of the important components in early childhood language development, which is related to children’s ability to understand, mention, and use words in daily communication. The results of the initial observation indicated that the vocabulary ability of children aged 4–5 years at TK ABA Somawangi was still in the low category. This study aims to improve the vocabulary ability of object nouns in children aged 4–5 years through the implementation of the bingo game. This research employed the Classroom Action Research (CAR) method conducted in two cycles with 15 children as research subjects. Each cycle consisted of planning, implementation, observation, and reflection stages. The results of the study showed a significant improvement in children’s vocabulary ability, as indicated by the average achievement of indicators which increased from 46.25% at the pre-research stage to 69.17% in Cycle I and reached 86.46% in Cycle II. Thus, it exceeded the research success indicator of 85%, and it can be concluded that the bingo game can improve the object vocabulary ability of children aged 4–5 years.